A percepção de idosos muito idosos, que sentem dor, sobre a necessidade de assistência para realização das atividades de vida diária - Fausto Henrique Dias (2018)
The world population experiences a gradual process of aging that is related to the improvement of health conditions and quality of life with a consequent increase in life expectancy. In Brazil there was also a change in the age profile and the group that grows the most is composed of elderly people aged 80 and over, called elderly people. With this change in the age profile there is an increase in non-transmissible chronic-degenerative diseases which can present pain as a common symptomatology and cause a process of functional incapacity. Pain is a subjective experience, influenced by the social and cultural context.The elderly person who feels pain may have limitations and need help to perform their daily activities. The levels of care may vary from verbal support where there is encouragement to perform the activity, the total assistance, in which the activity is performed for the person. The objective of this study was to understand the perception of the elderly, who feel pain, about the need to receive assistance in activities of daily living. A qualitative study performed with the elderly of 80 years and older, recruited from the multicenter, international Back Complaints in the Elderly (BACE) study. Data were collected through semi-structured interviews and the number of participants was defined by the saturation criterion. Thematic content analysis was used to analyze the data. Thirty-two elderly, 30 women and two men aged 80 to 91 years participated in the study. After careful analysis of the interviews two categories emerged: "Need for day-to-day assistance of the elderly with pain" and "I want help, but who can help?". Participants stated that they need total assistance to carry out instrumental activities of daily living, related to home care and mobility. They also pointed out that the help provided came from their relatives, neighbors, and that if it was not possible an alternative was to pay for assistance. Knowledge of these results may contribute to the need for formal and informal health professionals and caregivers to broaden their understanding of the demands of the elderly and the complex process of care during the performance of daily activities. And so they can intervene considering the subjectivity of pain and the wide spectrum of assistance modalities with the elderly very old.